Lean and BIM Implementation Barriers in New Zealand Construction Practice - Likita AJ; Jelodar MB; Vishnupriya V; Rotimi JOB; Vilasini N (MDPI AG, 2022)
The construction sector is lagging behind other industries in terms of efficiency and value achievement. Several building sector initiatives are introduced to improve productivity and project value enhancement. Significant developments such as Lean principles and BIM tools have been applied in the construction sector to achieve efficiency and enhanced productivity while minimizing waste. Lean principles in construction practice are a developing research area, and BIM tools have been widely used in construction project delivery and communications. Although these concepts are beneficial, barriers to their integration and joint implementation have not previously been explored. The paper investigates barriers to implementing Lean and BIM and their interrelationships in the New Zealand construction industry. A three-step triangulation methodology was used in the study to validate the findings. The study used an extensive literature review process, case studies, and expert interviews to consolidate the findings. Barriers to Lean and BIM implementation in construction practice were identified, which include strong cultural resistance, lack of Lean-BIM understanding, resistance to change, lack of knowledge of the Lean-BIM method, and lack of support from senior staff in New Zealand organizations. The effect of implementing Lean-BIM principles is discussed, as are recommendations for implementing the method in construction practice.
Keywords: 1201 Architecture; 1202 Building; 1203 Design Practice and Management